Parental rejection and generalized anxiety disorder in early adolescents: the mediating role of alexithymia - Fabris, Matteo Angelo; Longobardi, Claudio; Zdankiewicz-Ścigala, Elżbieta; Ścigała, Dawid Konrad (Frontiers in Psychology, 2025)
The aim of this study is to extend our knowledge of the possible association between (maternal and paternal) parental rejection and generalized anxiety disorder (GAD) symptoms in early adolescence by investigating the possible mediating role of alexithymia. A sample of Italian early adolescents (N = 234; Mage: 11.86, SD = 0.93; 47% male) was recruited from several schools in northwestern Italy. Participants completed an anonymous self-report questionnaire that included information on experience of parental rejection, alexithymia, and GAD symptoms. Our results show an association between parental rejection (both maternal and paternal) and GAD symptoms. Furthermore, the data show that alexithymia tends to mediate the relationship between maternal/paternal rejection and GAD. In this sense, parental rejection is associated with an increase in alexithymic symptoms, which in turn is associated with an increase in GAD symptoms in early adolescents. Limitations of the research and practical implications are discussed.